Soviet Lithuanian press and publications for foreign readers (1940-1975) - Starkūnaitė-Jurkuvėnienė, Vanda (Knygotyra, 2026)
In the analysis of the complex problem of the spread of the Soviet Lithuanian press abroad the attention is focused on the periodicals and other publications of our Republic which come out in Lithuanian, Russian, and foreign languages. Foreign readers know our books, booklets, brochures, advertising booklets, magazines, newspapers, and scientific and academic publications. These publications differ in character: some of them are meant for the population of the Republic, others for foreign guests, i. e., tourists, while a definite number of academic and scientific publications are disseminated among foreign scholars and scientists; a number of books and newspapers are intended for foreign readers mostly of Lithuanian origin. Most of the Soviet Lithuanian publications and periodicals are available to foreign readers. The analysis of the problem also reveals the state of book publishing in the Republic.